Differences in the key volatile organic compound species between their emitted and ambient concentrations in ozone formation - X. Zheng; X. Zheng; S. Xie (Atmospheric Chemistry and Physics)
The emissions and secondary transformations of volatile organic compounds (VOCs) play a significant role in ozone (O3) formation. Previous studies have often relied on ambient VOC concentrations to identify key species. However, ambient concentrations represent the residual concentrations after the emitted VOCs have been consumed, which can introduce substantial uncertainties. To address this issue, this study proposes a novel method to identify the key VOC species in both anthropogenic and biogenic emissions. The emitted VOC concentrations are calculated during both nighttime and daytime in summer using the nitrate radical, O3, and hydroxyl radical reaction rates and ambient concentrations of 99 VOCs measured at Deyang, Chengdu, and Meishan, China. The emitted concentrations of alkenes and aromatics are higher than the ambient concentrations. The largest differences between emitted and ambient concentrations are 1.04 ppbv for cis-2-butene at Deyang, 0.81 ppbv for isoprene at Chengdu, and 1.79 ppbv for isoprene at Meishan. In contrast, due to secondary production, the emitted concentrations of oxygenated VOCs are lower than the ambient concentrations. The largest differences are −0.54 ppbv for acetone at Deyang, −0.58 ppbv for acetaldehyde at Chengdu, and −0.5 ppbv for acetone at Meishan. Based on the emitted concentrations, isoprene is one of the top three species contributing to O3 formation at all three sites, which may be overlooked in observed concentrations. Comprehensive calculation of the emitted VOC concentrations enables the key VOC species in O3 formation to be accurately identified.